Mediating Role of Corporate Image in the Relationship between Service Quality and Customer Satisfaction: A Study of PT. Pelindo Energi Logistik: Peran Mediasi Citra Perusahaan dalam Hubungan antara Kualitas Pelayanan dan Kepuasan Pelanggan: Studi pada PT. Pelindo Energi Logistik - Kristiawati, Indriana; Ester Kalangi, Meyti Hanna; Utomo, Utomo (Indonesian Journal of Law and Economics Review, 2023)
This quantitative research aimed to investigate the relationship between service quality, corporate image, and customer satisfaction at PT. Pelindo Energi Logistik. The study utilized path analysis and Sobel test to analyze the data collected from a sample of 30 companies who were customers of PT. Pelindo Energi Logistik. The findings revealed that service quality significantly influenced corporate image (p < 0.05) and customer satisfaction (p < 0.05). Additionally, corporate image had a significant impact on customer satisfaction (p < 0.05). Moreover, corporate image was found to mediate the relationship between service quality and customer satisfaction, indicating its crucial role in strengthening the effect of service quality on customer satisfaction. These results emphasize the importance of enhancing service quality and maintaining a positive corporate image to ensure customer satisfaction in the logistics industry. The study contributes to the existing body of knowledge by providing valuable insights for global researchers and professionals in the field of service quality, corporate image, and customer satisfaction in the logistics sector. Highlight: Service quality significantly influences company image, indicating the impact of service provision on the perception of the company. Service quality plays a crucial role in determining customer satisfaction, emphasizing the importance of delivering satisfactory services to meet customer expectations. The company's image significantly affects customer satisfaction, underscoring the role of a positive corporate image in enhancing customer satisfaction levels. Keyword: Company Image, Service Quality, Customer Satisfaction, Mediation, Logistics Industry